Association of Biofilm Formation with Antimicrobial Resistance Among the Acinetobacter Species in A Tertiary Care Hospital in Bangladesh (Journal of Medicine, 2013)
Purpose: The purpose of this study was to detect biofilm formation in clinical isolates of Acinetobacter species and to observe correlation between biofilm formation and antimicrobial resistance among Acinetobacter isolates. Methods: Two hundred fifty six clinical samples collected from patients who were admitted in Intensive Care Unit (ICU) and on device, patients from Surgery, Medicine, Gynae & Obs and Urology department of Bangabandhu Sheikh Mujib Medical University (BSMMU) and from Burn unit of Dhaka Medical College Hospital were included in this study. Biofilm formation and antibiotyping were performed for the isolates of Acinetobacter species recovered from clinical samples including tracheal aspirates, blood, urine, wound swab, pus, throat swab, endotracheal tubes, burn samples, ascitic fluid, sputum, aural swab, oral swab, cerebrospinal fluid, and catheter tip. Correlation of biofilm formation with antimicrobial resistance pattern among Acinetobacter isolates were also observed in this study. Result: A total of 256 various specimens were studied of which 95 Intensive Care Unit (ICU) and 161 Non ICU samples. Out of 95 ICU and 161 Non ICU samples, Acinetobacter species were isolated from 32 (33.7%) and 20(12.4%) respectively. From 32 ICU and 20 Non ICU Acinetobacter isolates, 28 (87.5%) and 11 (55%) were biofilm producers. Biofilm forming capacity of Acinetobacter species was significantly (p